2021
DOI: 10.1126/science.abk3099
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Birch reduction with lithium and ethylenediamine in tetrahydrofuran

Abstract: Easy aryl reductions The Birch reduction has been widely used for more than half a century to achieve partial reduction of aryl rings by alkali metals at just two diametrically opposed carbon sites. However, the conditions require condensation of caustic gaseous ammonia. A variation developed soon afterward by Benkeser used safer liquid ethylene diamine but was prone to overreduction. By diluting ethylene diamine in tetrahydrofuran solvent, Burrows et al . now obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 78 publications
1
80
0
Order By: Relevance
“…In fact, lithium's low reduction potential allows for it to be easily ionized in the presence of strongly Lewis basic ligands such as ammonia or alkylamines. 24,25 During this type of dissolution process the s electron from Li-metal is ionized into solution which leads to the characteristic blue hue of a solvated electron under relatively dilute conditions and a fiery bronze color at high concentrations (Figure 1D). Understanding the fundamental nature of the alkali metal electrides has been an ongoing topic of research for over a century.…”
Section: Formation Of Lithiummentioning
confidence: 99%
“…In fact, lithium's low reduction potential allows for it to be easily ionized in the presence of strongly Lewis basic ligands such as ammonia or alkylamines. 24,25 During this type of dissolution process the s electron from Li-metal is ionized into solution which leads to the characteristic blue hue of a solvated electron under relatively dilute conditions and a fiery bronze color at high concentrations (Figure 1D). Understanding the fundamental nature of the alkali metal electrides has been an ongoing topic of research for over a century.…”
Section: Formation Of Lithiummentioning
confidence: 99%
“… 14 The harsh and challenging conditions of this methodology mean that it is not favored in industrial settings as it presents several safety challenges with copious amounts of ammonia required upon scale-up. 15 , 16 While there have been several efforts to produce an ammonia-free Birch reduction, the methodologies have only been demonstrated on small scales 17 19 and in some cases, they led to over-reduction of the Birch-type products. 20 22 A recent report by Koide and co-workers demonstrated that a Birch reduction could be achieved by replacing ammonia with ethylenediamine in THF and lithium metal as the reducing agent.…”
Section: Introductionmentioning
confidence: 99%
“…We have been interested in the development of alkali-metal-promoted reductive transformations of unsaturated compounds [20][21][22][23][24] by using reduction-resistant electrophiles as key reagents. [25][26][27] In one hand, this class of electrophiles such as trialkoxyboranes are resistant to single electron reduction so that they can coexist in the same pot where the reduction of unsaturated substrates takes place.…”
Section: Introductionmentioning
confidence: 99%